O primeiro Manoel de Barros e o aprendizado poético - Ferrari, Viviane de Cássia Duarte (2014)
The problem articulated in this work is to understand how the mato-grossense poet Manoel de Barros has been produced a modern poetry since the start of his career, when he had published the books Poemas concebidos sem pecado (1937) e Face imóvel (1942). To identify such a question, it will support, first in an overview of the barreano themes and stile, following, it will be done interpretative analysis of some poems from both books, in order to see if the modern aspects presented as marks on his poetry have already appeared since the beginning of his writings and if changes occurred in these traits throughout his literary creations. Thus, this research will verify the guiding-up elements of his first poetry, in order to establish relations between his initial poetic project and the rest of his works. This interpretative and comparative approach will contribute to the understanding and affinities of his unconventional lyrical. As it was seen here, both the recurrence of certain themes and some peculiarities of barreano style, it can show various signs of modernity which, in turn, helped to single out his poetics.